Development of a Monte-Carlo Evaporation Code for Multiple-Fragment Emission - Nicolis, N. G. (HNPS Advances in Nuclear Physics, 2021)
An extended Hauser-Feshbach approach has been employed in a multi-step Monte-Carlo evaporation code designed to study the de-excitation of highly excited compound nuclei. The code is intended to account for emission of light particles ($γ$, n, $^{1,2,3}$H, $^{3-6}$He) and intermediate mass fragments in their ground and excited states (particle-bound or unbound). As a study case, we consider the decay of the compound nucleus $^{120}$Te$^*$ at excitation energy 100, 200 and 300 MeV. First chance decay widths are compared with treatments based on the Weisskopf and the s-wave approximation. Preliminary calculations are compared with experimental isotopic yields of intermediate mass fragments emitted in E/A = 50 MeV $^{4}$He + $^{116,124}$Sn $→$ $^{120,128}$Te$^*$ reactions.